Evaluation of life quality and health behaviors of patients with stable coronary artery disease in the geriatric age - Kózka, Maria; Majda, Anna; Kula, Anna (Nursing Problems / Problemy Pielęgniarstwa, 2013)
Introduction. Polish society is aging, and the presence of stable coronary artery disease increased with age in both sexes. Lack of healthy behaviors is one of the factors affecting increase of lifestyle diseases increase, including coronary heart disease. In the era of modern medicine and human life time prolongation, an interest in older people life quality has gained on importance. Aim of the study . Evaluation of life quality and health behaviors of patients with stable coronary artery disease in the geriatric age. Material and methods. I studies patients with diagnosed stable coronary artery disease. Overall, 72 patients were tested. During the research WHOQOL-BREF quality of life scale and the Health Behavior Inventory by Juczyński were used. Results. Over half of the respondents (51.39%) were happy with their quality of life, and 19,44% were dissatisfied with their health. Average health behaviors studies were 5.58 (SD = 1,74). It is average result. Studies have shown a highly significant (p < 0.001) correlation (r = 0.3944) between the overall perception of quality of life of the represents and their positive psychical attitude. Conclusions. Represents were more satisfied with the quality of their life, than with the quality of healthcare. There are differences in the assessment of various aspects of life among the respondents. Top rated were the social relations, while the lowest rates concerned physical sphere. The quality of life of respondents had a statistically significant effect: stage of disease and a positive psychical attitude.